Remapping Englishness in Peter Ackroyd’s Milton in America - Farahmandfar Masoud (Romanian Journal of English Studies, 2022)
Peter Ackroyd’s historiographic metafictional novel Milton in America (2006) entails a critical return to history – critical in the sense that it questions the essence of historical knowledge and revisits the past in order to comment on the politics of national identity. Beneath a façade of historicity, the novel explores the continuity of English cultural identity and narrates a fictional story that centres on the conflict of Catholicism and Protestantism in the context of post-Restoration emigration of Puritans from England to New England. The “old faith”, although marginalized, continued to exist in post-Reformation England. The novel ties the significance of Catholicism to a thorough sense of Englishness. Catholic faith is shown as an ancient anchor of English identity. Peter Ackroyd delves into the collective memory of his race in search of a sense of commonality, believing in the continuity of English national identity. Challenging humanist assumptions about historical authenticity, the novel calls into question the idea of religious homogeneity, offering a different narrative as equally valuable.